English language teachers’ professional development and identities (2014)
This article analyzes the professional development of two English language teachers in a Mexican language center. In particular, it explores the interplay between professional development, identity and agency, and the part played by English language teaching certificates in all of these. Drawing on a case study methodology, which included the use of a series of three interviews and other qualitative data collection methods, the article demonstrates the intimate and intricate connection between teachers’ identities and their professional development. Education implications for policy makers and practitioners are discussed.Este artículo analiza el desarrollo profesional de dos profesoras del idioma inglés en un centro de lenguas de una universidad pública mexicana. En particular, el trabajo explora la relación entre desarrollo profesional, identidad y agencia. Se utiliza la metodología de estudio de casos, la cual incluye el uso de entrevistas biográficas y otros métodos de recopilación de datos cualitativos. Los resultados hacen evidente la íntima relación que existe entre la identidad de los profesores y su desarrollo profesional. Se presentan las implicaciones del estudio para los desarrolladores de políticas educativas, los tutores de programas de desarrollo profesional e investigadores.